(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: The palmyra (Borassus flabellifer L.) is a member of the Arecaceae family. The unfermented palmyra tree sap, or neera, is used to make jaggery. Antimicrobials are substances that kill or inhibit the growth of harmful microorganisms like bacteria, viruses, fungi, and parasites. The study focuses on elucidating the antimicrobial properties of palm jaggery by analyzing the bioactive metabolites identified through High- Resolution Accurate Mass Spectrometry (HRMS). Methodology: The optimised sample of Palm jaggery was tested for metabolomics analysis. The High-Resolution Accurate Mass Spectrometry system instrument with the model name Orbitrap Eclipse Tribrid Mass Spectrometer developed by Thermo Fisher Scientific was used for the analysis of Palm jaggery sample. The raw data obtained from the mass analyser were performed through default parameters of “Compound discoverer 3.3.2.31” using online databases. Result: Utilizing HRMS, we successfully identified a diverse array of bioactive compounds and other secondary metabolites. This study has identified four key metabolites namely Diselane, Selenophosphate, Cadmium Sulfide, and Carnosol as having notable antimicrobial properties. The reported antimicrobial efficacy of these components was systematically evaluated and previous studies revealed significant antibacterial activity, particularly against both Gram-positive and Gram-negative strains. Conclusion: Reported findings not only enhance the understanding of palm jaggery’s biochemical profile but also highlight its significance as a source of antimicrobial agents, warranting further exploration for applications in food preservation and healthcare. This study contributes to the growing body of knowledge regarding the functional properties of traditional foods and their role in promoting public health.